1980
DOI: 10.1111/j.1600-0765.1980.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscope quantitation of inflammatory infiltrates in childhood gingivitis

Abstract: Quantitation of inflammatory cell infiltrates in gingival connective tissues was carried out on 12 gingival biopsies from the deciduous dentition of 11 children aged 4–8 years. The tissue was prepared for electron microscopy and from ultrathin sections mounted on 200 mesh grids, cells in one third of the grid squares enclosing infiltrated connective tissue were counted. The infiltrate displayed large numbers of small and medium lymphocytes and was moderately vascular. A distinct population of peripherally dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
4
22
1
Order By: Relevance
“…Using methyl green-pyronin stain on sections of inflamed gingiva from adults and children, they found that small and medium-sized lymphocytes predominated in the latter group. Our findings are, however, at some variance with the observations of Longhurst et al (1980). On the basis of electron microscopic observations which demonstrated a relative lack of transforming T lymphocytes Table 2.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Using methyl green-pyronin stain on sections of inflamed gingiva from adults and children, they found that small and medium-sized lymphocytes predominated in the latter group. Our findings are, however, at some variance with the observations of Longhurst et al (1980). On the basis of electron microscopic observations which demonstrated a relative lack of transforming T lymphocytes Table 2.…”
Section: Discussioncontrasting
confidence: 56%
“…The proportion of plasma cells appears to increase with increasing severity of inflammation (Lindhe et al 1980). Immunohistochemical studies indicate that there is a gradually increasing proportion of plasma cells producing IgG with increasing severity of the inflammatory changes (Brandtzaeg & Tolo 1977), Longhurst et al, (1977Longhurst et al, ( , 1980 and Seymour et al, (1981) have presented studies based on morphological methods which may indicate that in children, the gingival inflammatory infiltrate contains a higher proportion of lymphocytes than usually seen in CIPD in adults, , on the basis of histochemical and immunofluorescence studies, have presented evidence suggesting that the change from a stable to a destructive lesion may involve a shift from a T cell to a B cell (plasma cell) dominated lesion. However.…”
mentioning
confidence: 99%
“…trated connective tissue, facilitating such a transformation. The time-scale of this change was once considered to be a matter of 2-4 weeks in man (Payne et al 1975, Page & Schroeder 1976, but this was based mainly on extrapolation from experimental studies in animals and it is now clear that such a transition may take much longer in man (Zachrisson 1968, Longhurst et al 1980, Seymour et al 1983a. The transition time probably varies considerably in the different forms of periodontal disease and at different tooth sites within and between patients.…”
Section: Gingivitismentioning
confidence: 99%
“…The transition time probably varies considerably in the different forms of periodontal disease and at different tooth sites within and between patients. The rapid tissue destruction, marked and consistent plasma cell domination seen in Juvenile Periodontitis , Davenport et al 1982, Longhurst et al 1977, Gillett & Johnson 1982, Gillett et al 1986) perhaps reflects a rapid transition, whilst in childhood gingivitis progression of disease and the transformation of B-lymphocytes to active plasma cells appears to be indefinitely delayed (Longhurst et al 1977, Longhurst et al 1980, Gillett et al 1986, Walsh et al 1987. Brecx et al (1987b) have recently shown that even when 3 to 4 weeks of meticulous professionally administered oral hygiene has rendered the gingiva healthy as judged by clinical evaluation.…”
Section: Gingivitismentioning
confidence: 99%
See 1 more Smart Citation